Active zone plasticity couples sleep need to presynaptic hypophosphorylation - Chengji Piao; Ewelina P. Dutkiewicz; Laxmikanth Kollipara; Albert Sickmann; Sheng Huang; Stephan J. Sigrist (Proceedings of the National Academy of Sciences, 2026)
Sleep need is associated with both circuit dynamics and widespread synaptic plasticity, yet the specific synaptic changes underlying sleep homeostasis remain incompletely understood. In Drosophila , sleep loss has been shown to trigger plasticity of the presynaptic active zone, marked by increasing levels of the ELKS-family scaffold protein Bruchpilot (BRP). By titrating brp gene copy number, we previously established a presynapse-specific, dosage-dependent paradigm that modulates sleep pressure. Here, to elucidate the molecular landscape of this plasticity, we performed synapse-enriched integrated-omics. Proteomic and bioinformatic analyses revealed changes in immune and stress response pathways and local translation control. Strikingly, phospho-proteomic analysis uncovered a global shift toward hypophosphorylation, particularly in presynaptic proteins, indicating a reprogramming of the phosphorylation–dephosphorylation balance. This presynaptic hypophosphorylation is likely contributed by reduced activity of Protein Kinase A (PKA) and enhanced substrate affinity of Protein Phosphatase 1 (PP1) mediated by its regulatory subunit Spinophilin (Spn). Manipulating either PKA or PP1 activity was sufficient to suppress BRP-modulated sleep phenotypes. We propose that presynaptic hypophosphorylation constitutes a molecular signature of local synaptic remodeling that adaptively tunes sleep need via reversible posttranslational modification, a mechanism likely conserved across species.